The fabla salvaje of the patriarchal civilisation - Westphalen Rodríguez, Yolanda (2023)
This article examines César Vallejo’s Fabla salvaje, published in 1923, in the context of patriarchal civilisation in early twentiethcentury Peru. It explores the social and cultural background of the time, marked by peasant uprisings, indigenous movements, university activism and changing gender roles. The representation of masculinity and femininity in the novel is analysed, with special attention to the psychological conflict of the protagonist Balta and his projection of patriarchal cultural norms onto his wife Adelaida. It also questions the interpretation of Balta’s internal conflict as the result solely of personal psychological disturbances; and proposes an alternative perspective that sees it as a manifestation of entrenched cultural patterns of masculinity in the context of a neocolonial modernity. Through careful textual analysis, the article delves into the complexities of gender dynamics, hybrid modernities and the tension between traditional and emerging norms of society, ultimately suggesting that Balta’s tragic fate embodies the conflicts and failures of the patriarchal order in a changing Peruvian landscape.